Retirement effects of heavy job demands - Golo Henseke (Universität Rostock, Institut für Volkswirtschaftslehre, 2011)
This study focuses on the influence of heavy job demands on retirement, using the available SHARE waves. Heavy job demands may have a direct and health mediated effect on individual retirement. An econometric challenge is the dynamic self-selection of workers into jobs. The main findings indicate: the frequency of heavy job demands is higher among workers with low levels of socioeconomic status. Heavy job demands are associated with on average higher retirement probabilities, once workers become eligible to pension benefits. The effect is driven by long-term exposure to heavy job demands during the career. There are overall no retirement effects in the age bracket 50-58 and thus no indication for strong adverse health effects. A change in the level of current job demands does not influence the subsequent probability of retirement.
Keywords: J26; J28; C26; 330; Health; job demands; selection bias; Altersgrenze; Arbeitsnachfrage; Stress; Schätzung; Europa